The bases of derivation of Old English affixed nouns: Status and category - González Torres, Elisa (Adam Mickiewicz University, 2010)
The aim of this journal article is to carry out a complete analysis of the category, status and patterns of the bases of derivation of Old English affixal nouns. The results of the analysis are discussed in the light of the evolution from stem-formation to word-formation. The corpus of analysis of this research is based on data retrieved from the lexical database of Old English Nerthus, which contains 30170 predicates. 16694 out of these are nouns, of which 4115 are basic and 12579 qualify as non-basic. Within non-basic nouns there are 3488 affixed nouns (351 by prefixation and 3137 by suffixation) and 9091 compound nouns. The line of argumentation is that, under certain circumstances, the existence of more than one base available for the formation of a derivative does not reinforce the explanation of invariable bases; on the contrary, it goes in the direction of variable bases produced by inflectional processes and made ready for derivation. The following conclusions are reached. In the first place, the importance is underlined of formations on stems in Old English, involving, at least, nouns. Secondly, the analysis evidences that the importance of stem-formation in Old English might be higher than has been acknowledged by previous studies. If Old English made extensive use of words as bases of derivation, a single base should be available; if, on the contrary, Old English is still dependent on stem-formation, more than one base is likely to be found for a single derivative. Such alternative bases of derivation reflect stemformation that may result from inflectional means and be eventually used for derivational purposes.